Extractive stripping voltammetry at a glassy carbon paste electrode for analysis cow's milk and cream - Jashari, Granit; Frühbauerová, Michaela; Sýs, Milan; Červenka, Libor (My University, 2020)
In this paper, a procedure based on extractive accumulation of milk fat globules (MFGs) into a pasting liquid (lipophilic binder) of glassy carbon paste electrode (GCPE) with subsequent electrochemical detection by square-wave voltammetry (SWV) in 0.1 mol L-1 Britton-Robinson buffer of pH 4.0 has been tested to find out whether it can be utilized as a simple screening analytical method for cow's milk and cream nutrition control. Since there is assumption that the necessary alkaline hydrolysis of cow's milk and subsequent extraction of lipophilic vitamins into an organic solvent could be avoided, several GCPEs differing in type (atactic polypropylene, paraffin oil, paraffin wax, silicone oil, and vaseline) and content (5, 10, 15, 20, and 25%; w/w) of pasting liquid used were tested as part of complex optimization. The obtained results show that MFGs contain predominantly vitamin A (carotenoids and retinoids), especially all-trans-retinol, which could serve as significant marker of the fat content. However, their individual forms were not possible to distinguish due to the considerable anodic peak broadening (overlapping).
Extraktivní stripping voltametrie na pastové elektrodě ze skelného uhlíku pro analýzu mléka a smetany
Keywords: carbon paste electrode; cow's milk; extraction; milk fortification; nutrition control; voltammetry; uhlíková pastová elektroda; kravské mléko; extrakce; fortifikace mléka; kontrola nutričních hodnot; voltametrie